2010
DOI: 10.1186/1471-2261-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Human macrophage foam cells degrade atherosclerotic plaques through cathepsin K mediated processes

Abstract: BackgroundProteolytic degradation of Type I Collagen by proteases may play an important role in remodeling of atherosclerotic plaques, contributing to increased risk of plaque rupture.The aim of the current study was to investigate whether human macrophage foam cells degrade the extracellular matrix (ECM) of atherosclerotic plaques by cathepsin K mediated processes.MethodsWe 1) cultured human macrophages on ECM and measured cathepsin K generated fragments of type I collagen (C-terminal fragments of Type I coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
1
30
0
1
Order By: Relevance
“…The destructive role of cathepsin K in macrophage foam cells was confirmed by immunohistochemical analysis that revealed accumulation of collagen type I degradation products close to cathepsin K immunoreactivity. These results were supported by an in vitro experiment where incubation of human macrophage foam cells on a collagen matrix resulted in the accumulation of collagen degradation products (Barascuk et al, 2010). Cathepsin K expression in endothelial cells in human atherosclerotic plaques also correlated with internal elastic lamina destruction (Platt et al, 2007).…”
Section: Atherosclerosissupporting
confidence: 71%
“…The destructive role of cathepsin K in macrophage foam cells was confirmed by immunohistochemical analysis that revealed accumulation of collagen type I degradation products close to cathepsin K immunoreactivity. These results were supported by an in vitro experiment where incubation of human macrophage foam cells on a collagen matrix resulted in the accumulation of collagen degradation products (Barascuk et al, 2010). Cathepsin K expression in endothelial cells in human atherosclerotic plaques also correlated with internal elastic lamina destruction (Platt et al, 2007).…”
Section: Atherosclerosissupporting
confidence: 71%
“…It has been demonstrated that foam cells, a pathological finding in lipid-rich atherosclerotic plaques, are able to produce active cathepsin K and release CTX [5]. Collagen turnover in the caps of vulnerable plaques has been implicated in their propensity to rupture [17], leading to myocardial infarction.…”
Section: Acsmentioning
confidence: 99%
“…The role of cathepsins in the heart is emerging. It has been demonstrated that foam cells in atherosclerotic plaques within the cardiac vasculature are capable of producing active cathepsin K [5].…”
Section: Acsmentioning
confidence: 99%
See 1 more Smart Citation
“…An imbalance between cystatin C and cathepsins may trigger a pathophysiological cascade leading to atherosclerosis 214 and collagen degradation in the cap of the atherosclerotic plaque, increasing the risk of rupture. 215,216 Levels of cathepsins are elevated in STEMI patients at arrival. 217 Additionally, cathepsins are probably involved in healing process after STEMI and cathepsin-mediated turnover of collagen is increased during the first days following the myocardial infarction.…”
Section: Gfr Estimations In Stemi Patients During the Initial Hospitamentioning
confidence: 99%